Pengaruh pelatihan keterampilan komunikasi interpersonal dalam meningkatkan self-esteem pada siswa - Sinurat, Siti Farida; Furqoni, Prima Dian; Elliya, Rahma; Wahyudi, Wahid Tri (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Self-esteem is a very important psychological aspect in adolescent development, especially in the digital era which is full of challenges and changes. In adolescence, individuals begin to form their self-identity, and self-esteem plays a central role in this process. Purpose: To determine the effect of Communication Skills Training on the Self-Esteem of students. Method: This research is a quantitative study using a pre-experimental design with a one-group pretest–posttest approach. The research subjects were 21 tenth-grade students of SMK Persada Bandar Lampung, selected using the total sampling technique. Data analysis was conducted using univariate and bivariate analysis with a dependent t-test. Results: The average Self-Esteem of students before receiving communication skills training is 19.05 with a standard deviation of 4.873, and after receiving communication skills training, it increased to a mean of 44.33 with a standard deviation of 7.631. The statistical test result shows a value of 0.000. Conclusion: There is a significant effect of communication skills training on enhancing self-esteem among students at SMK Persada Bandar Lampung in 2025. It is hoped that students can improve interpersonal communication well and appropriately to enhance their self-esteem. Keywords: Communication Skills; : Self-Esteem; Training. Pendahuluan: Self-esteem atau harga diri merupakan aspek psikologis yang sangat penting dalam perkembangan remaja, terutama di era digital yang penuh tantangan dan perubahan. Di masa remaja, individu mulai membentuk identitas diri mereka, dan self-esteem memainkan peran sentral dalam proses ini. Tujuan: Untuk mengetahui pengaruh Pelatihan keterampilan komunikasi terhadap Self Esteem siswa siswi. Metode: Penelitian kuantitatif dengan menggunakan desain Pra Eksperimental menggunakan pendekatan One group Pretest-Posttest. Subjek penelitian adalah 21 siswa kelas X SMK Persada Bandar Lampung yang dipilih dengan teknik total sampling. Analisa data analisis univariate dan bivariate dengan Uji t-dependen. Hasil: Rata-rata Self-Esteem Pada Siswa sebelum diberikan pelatihan keterampilan komunikasi adalah 19,05 dengan standar deviasi 4.873 dan setelah diberikan pelatihan keterampilan komunikasi mengalami peningkatan dengan mean 44.33 dengan standar deviation 7,631. Hasil uji statistik didapatkan nilai p-value 0,000. Simpulan: Terdapat pengaruh yang signifikan pelatihan keterampilan komunikasi dalam meningkatkan self-esteem pada siswa. Kata Kunci: Harga Diri; Keterampilan Komunikasi; Pelatihan.